Answer:
The answer to your question is:
Step-by-step explanation:
Data
f(x) = -2x² + 8x - 2
Process
-2x² + 8x = y + 2
-2(x² - 4x + 4) = y + 2 - 8
-2(x - 2)² = y - 6
(x - 2)² = 1/2 (y - 6)
Vertex = (2, 6)
Axis of symmetry = x = 2
y-intercept
f(0) = -2(0)² + 8(0) - 2
f(0) = 0 + 0 - 2
f(0) = -2
Domain (-∞, ∞)
Range (-∞, 6]
See the graph below
The <em>correct answer</em> is:
D) reflect over the y axis and then reflect again over the y axis.
Explanation:
Logically, if we reflect a figure across the y-axis and then reflect across the y-axis again, we have undone what we originally did, and the figure is back in its original position.
Algebraically, reflecting across the y-axis maps every point (x, y) to (-x, y). Reflecting this point across the y-axis maps (-x, y) to (x, y); this is our original point.
Add 26 to each side of the equation !
Since both equations equal Y, set them equal to each other and solve.
3x -1 = -2x +9
Add 2x to each side:
5x - 1 = 9
Add 1 to each side:
5x = 10
Divide both sides by 5:
x = 10/5
x = 2
Now replace x with 2 and solve for y:
y = 3(2) -1 = 6-1 = 5
x = 2, y = 5 (2,5)